The role of laparoscopic approach in bilaterality assessment in patients with unilateral inguinal hernia - Marzouk, Ahmed M. S. M.; Omar, Haitham S. E.; Ali, Heba O. E. (International Surgery Journal, 2017)
Background: Patients presented with unilateral inguinal hernia are at risk for the possibility of contra-lateral occult hernias; small early-developed hernias may be difficult to be elicited by clinical, imaging assessment and during open repair. This study to evaluate laparoscopic identification of contra-lateral occult hernia with regard to the pre-operative clinical and imaging study. Methods: Retrospective analysis of patients presented in the period of March to December 2015 with unilateral inguinal hernia for which medical and ultrasound imaging assessment were done. Laparoscopic trans abdominal pre-peritoneal (TAPP) approach was done with intraoperative evaluation of the presence of contra-lateral occult hernias. Results: During the study period (27) patients (25 Males and 2 females) presented with unilateral inguinal hernia were clinically evaluated, 18 (66.6%) patients had right sided hernia, 9 (33.33%) had left sided, In all the studied patients routine ultrasound assessment was done and no documented cases of presence of contra-lateral hernia, Intraoperative abdominal exploration successfully Identifies bilateral inguinal hernias in 7 cases (25.9%) with mean age (44.14 years, SD 10.99) compared to (34.97 years, SD 10.51) in the Unilateral group, 3 cases on the left side (16.6% of total right side patients) and 4 cases on the right side (44.4% of total left side patients). operative time for unilateral repair was (Mean 85.8 minutes, SD 18.8), and for discovered bilateral cases (Mean 145.9 minutes, SD 46.8). Conclusions: The presence of occult inguinal hernia is a frequent finding specially in older age group of patients, also in our study we found the percentage of occult hernias are more in patients presented with left side disease. Laparoscopic (TAPP) approach is a useful tool for assessment of the presence of such hernias, and gives the privilege of simultaneous repair in same operation with the advantage of avoiding the patient’s later surgery together with the laparoscopic surgery benefits of less pain, rapid recovery and shorter hospital stay.